Prevalence of Blue Spot among Mongolian Newborn Infants - Batbaatar, Suvd; Yadamsuren, Enkhtur; Sonom, Lkhamsuren; Unshigbayar, Oyunchimeg; Sharkhuu, Myagmarjav; Badrakh, Burmaajav (Central Asian Journal of Medical Sciences, 2017)
Objectives: The aim of this study was to determine the prevalence and characteristics of Mongolian spots in Mongolian infants. Methods: This hospital-based, descriptive cross-sectional study was conducted nationwide among 2641 newborn infants in Ulaanbaatar and in 21 provinces hospitals within 96 hours postpartum in 2015. Results: The prevalence of Mongolian spots in Mongolian infants was 91.3%. The prevalence of spots in females was 92.1% and in male newborns it was 90.6% (p>0.05). The prevalence of Mongolian spots in the Western provinces was lower than in the rest of other provinces (98.3% and 95% CI: 96.4-99.4). For of infants with Khalkha parentage, 92.7% had Mongolian spots, while 64.7% of infants with Kazakh parentage had Mongolian spots. The Mongolian spots are commonly located in infant’s lower back (88.3%) and had an average length of 3.7±2.7 cm, width of 2.7±1.9 cm and an average area of 14.2±23.3 cm2. The appearance of Mongolian spots on the infant’s legs, face, chest, hands, feet, knee, and cheeks were less frequent. Conclusion: The prevalence of Mongolian spots among Mongolian infants was 91.3% [95%CI: 87.2-95.3] and significant difference was observed between Mongolian and Kazakh infants.